DIALOG LINTAS AGAMA DAN UPAYA MENANGKAL POTENSI RADIKALISME DI KALANGAN PEMUDA - Ichwayudi, Budi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2020)
Radicalism is a religious understanding that has the potential to be present in every religion. Radical understanding is one of the ideas whose existence has received resistance from the community, even the state. In the context of Indonesia, radicalism is a challenge for the State to continue to be opposed, this is inseparable from the many theoretical cases masterminded by radical groups. Until now, the spread of radical understanding did not only reach adulthood, but had already begun to infect young people, even children. The younger generation as the nation’s next generation is very vulnerable to the spread of radical understanding, especially if the understanding is not accompanied by religious elites who have competence. This study uses a qualitative approach with interviews, observation and documentation as a technique to extract data. The results of the study stated that interfaith dialogue among youth in East Java as initiated by the Forum for Religious Harmony in East Java province is one of the strategic efforts to counteract the exposure of radical understanding among interfaith youth, by conducting dialogue the understanding of youth will be more open, nature exclusion in religion will collapse by understanding the existence of other religions as partners in social life, especially the fact that Indonesia is a plural nation is absolute, which we must maintain and respect each other in differences.Keywords: Interfaith Dialogue, Youth, Radicalism